Can Government Regulations in Lieu of Law Exceed Constitutional Limits? - Robert Yulion Ramualdo (Hakamain: Journal of Sharia and Law Studies, 2024)
This article aims to examine the constitutional limits governing the issuance of Government Regulations in Lieu of Law (Perppu) in Indonesia by analyzing the constitutional requirements of compelling necessity, presidential discretion, and legislative oversight within the framework of the 1945 Constitution. The study employs a normative legal research method using statutory, historical, conceptual, and case approaches. Primary legal materials include Article 22 of the 1945 Constitution, relevant legislation, Constitutional Court decisions, and historical records of Perppu issuance, complemented by secondary legal literature. The analysis covers 185 Perppu enacted from the Soekarno administration to the Joko Widodo administration, with particular emphasis on Perppu No. 1 of 2015 concerning the appointment of interim leadership of the Corruption Eradication Commission (Komisi Pemberantasan Korupsi—KPK) and Perppu No. 2 of 2022 on the Job Creation Law, subsequently enacted as Law No. 6 of 2023. The findings reveal that the interpretation of “compelling necessity” has gradually expanded through constitutional practice, increasing the scope of presidential discretion while making parliamentary approval an essential constitutional safeguard. The study concludes that the constitutional legitimacy of a Perppu depends not only on the existence of genuine emergency circumstances but also on effective legislative oversight and judicial review to preserve constitutional supremacy and the separation of powers. This article contributes to constitutional law scholarship by providing a comprehensive historical and doctrinal analysis of Indonesia’s Perppu practice and by proposing a clearer constitutional framework for balancing executive emergency powers with democratic accountability and the rule of law.